Tantangan dan Dinamika Sosial Hubungan Mertua-Menantu Perempuan Serumah Di Kelurahan Tamparang Keke Kota Makassar - Siti Arah Suniyah; Idham Irwansyah Idrus; Ulfa Utami Mappe (Universitas Halu Oleo (UHO), 2026)
The purpose of this study is to determine efforts to improve harmonious relationships over the challenges and dynamics that occur between in-laws and daughters-in-law who are influenced by various factors. Data collection was carried out using descriptive qualitative methods. Data were analyzed through several stages; 1) data reduction, 2) data presentation, 3) conclusion drawing and data verification. The results showed that the in-laws have many beliefs about the son-in-law who has a different point of view, there is poor communication because the wishes are not well expressed, so the division of labor becomes unclear which also spreads to privacy issues and unfulfilled boundaries. Implementing a collaborative approach by actively participating and cooperating in housework and being able to control emotions wisely can improve harmonious relationships. The conclusion of this study shows that the challenges of the relationship between in-laws and sons-in-law living in the same house are influenced by differences in values, ineffective communication, authoritarian roles, and privacy issues. The efforts to build harmonious relationships cannot all be implemented, but mainly through a collaborative approach and the ability to control emotions which proved to be the most effective in reducing conflict and strengthening cooperation.